Unlocking Women's Electoral Participation: Exploring the Impact of Education on Voter Participation in the General Elections of 2018 in Khyber Pakhtunkhwa (Pakistan) (Journal of Asian Development Studies, 2024)
This research paper investigates the multifaceted relationship between education and women's participation in electoral processes as voters. Through a comprehensive synthesis of existing literature, empirical studies, and theoretical frameworks, the study aims to unravel the intricate mechanisms by which education shapes women's engagement in elections. Furthermore, the research explores the mediating role of contextual factorsincluding socio-economic development, gender norms, and political institutionsin moderating the impact of education on women's voter turnout. By shedding light on these dynamics, the paper contributes to a deeper understanding of the complex interplay between education, socio-political contexts, and women's electoral behavior. This research holds implications for policy interventions aimed at promoting gender equality and fostering inclusive democratic practices worldwide